Ri-conoscersi nella differenza: Elementi per una lettura di genere dell'«Anerkennung» hegeliana - Chizzola, Valentina (Annali di studi religiosi, 2009)
Originally a basic concept of Hegel’s philosophy, the notion of recognition or Anerkennung has become a key concept in contemporary theorizing about issues of identity and difference and, more generally, of contemporary social, political and cultural theory. Beginning with a short survey of some different interpretations of the concept of Anerkennung that are to be found in current discussions I outline the significance of Hegel’s original notion by comparing it with an analysis of the concept of recognition brought forward by Judith Butler. My essay aims at showing how a reappraisal of Hegel’s notion of Anerkennung can provide a fruitful starting point for construing and understanding the complexity of gender-related identification processes.